Lançamento tributário: revisão e seus efeitos - Figueiredo, Marina Vieira de (2011)
For a rule to be legal, in other words, for it to join the system of positive law, it is essential the fulfillment of certain conditions. Once it entered the legal system, it is assumed that this rule is valid, ie, that it was enacted in accordance with the prescription of its base rule (rule of competence). In fact, we start from the premise that the production of a legal rule arises, always, from the appliance (incidence) of another rule, also legal, being essential that the created rule is subsumed to the rule which bases its creation. The problem is that the rules are not always enacted in accordance with the prescription of the higher rules (primary rules of competence). When the members of the system acknowledge that the rule is flawed that is, it was produced illicitly it is opened room for the application of the penalty provided by the secondary rule of competence: invalidity of the rule illegally created. Being the assessment a general and concrete legal rule which introduces into the system another rule, this one individual and concrete, responsible for the formation of the obligation to pay a specific tax it may have been enacted illegally. The review of the assessment is unveiled exactly when the taxable person, or the Treasury itself, believes that this rule is flawed whether related to the person that produced it, to the followed procedure in its drafting or to its contents (individual and concrete rule due the appliance of the tax incidence-matrix rule). Searching the rules which regulate the review of the assessment, as well as the possible defects to which is subdued, we verify that this not always leads to invalidity (not application) of that rule. We conclude, therefore, that, even if the assessment is claimed to be flawed, it may be: (i) sustained in its exact terms; (ii) refined (convalidation); (iii) or entirely or partially revoked. The review of the assessment, thus, does not always with its effacement from the system